Management of hyperhaemolysis after a transfusion in sickle‐cell patients. (29th January 2016) - Bartolucci, P.; Noizat Pirenne, F.; Habibi, A.
Abstract : Transfusion is a corner stone treatment of sickle cell disease complications. However one of the serious complications of transfusions is represented by the delayed haemolytic transfusion reaction (DHTR) with a significant mortality. It is due to a massive intravascular haemolysis of both transfused and autologous red blood cells. It occurs between 5 to 20 days after a transfusion and is accompanied by a vaso‐occlusive crisis and haemoglobinuria in almost all cases. The evolution can be life‐threatening because of the appearance of a severe acute chest syndrome or a multi organ failure. About half patients are transferred in Intensive Care Unit. The biological diagnosis of DHTR is made by the rapid decline, or disappearance, of Hb A in sickle cell patients who were previously transfused. This event is associated with a significant increase of lactico‐dehydrogenase (LDH) and worsening of anemia due to haemolysis. Allo antibodies are not found in 30%. DHTR is under diagnosed because of the delay between the transfusion and the symptoms, which mimic sickle cell vaso occlusive crises. This can lead to further transfusions that worsen the evolution and are ineffective. Because of the severity of this manifestation many treatment have been tried to improve the outcome as steroids, immunoglobulins, rituximab or eculizumab, without consensual guidelines. Early diagnosis of DHTR should help to decide the appropriate treatment, and avoid reiteration of transfusions. Transfusion indications should be maximally restricted in patients with previous post‐transfusion haemolysis.